The role of monoamine oxidase A in the neurobiology of aggressive, antisocial, and violent behavior: a tale of mice and men - Kolla, Nathan J. (Prog Neurobiol, 2020)
Over the past two decades, research has revealed that genetic factors shape the propensity for aggressive, antisocial, and violent behavior. The best-documented gene implicated in aggression is MAOA (Monoamine oxidase A), which encodes the key enzyme for the degradation of serotonin and catecholamines. Congenital MAOA deficiency, as well as low-activity MAOA variants, has been associated with a higher risk for antisocial behavior (ASB) and violence, particularly in males with a history of child maltreatment. Indeed, the interplay between low MAOA genetic variants and early-life adversity is the best-documented gene × environment (G × E) interaction in the pathophysiology of aggression and ASB. Additional evidence indicates that low MAOA activity in the brain is strongly associated with a higher propensity for aggression; furthermore, MAOA inhibition may be one of the primary mechanisms whereby prenatal smoke exposure increases the risk of ASB. Complementary to these lines of evidence, mouse models of Maoa deficiency and G × E interactions exhibit striking similarities with clinical phenotypes, proving to be valuable tools to investigate the neurobiological mechanisms underlying antisocial and aggressive behavior. Here, we provide a comprehensive overview of the current state of the knowledge on the involvement of MAOA in aggression, as defined by preclinical and clinical evidence. In particular, we show how the convergence of human and animal research is proving helpful to our understanding of how MAOA influences antisocial and violent behavior and how it may assist in the development of preventative and therapeutic strategies for aggressive manifestations.